Dimensional Analysis for Engineers - Simon, Volker; Weigand, Bernhard; Gomaa, Hassan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This monograph provides the fundamentals of dimensional analysis and illustrates the method by numerous examples for a wide spectrum of applications in engineering. The book covers thoroughly the fundamental definitions and the Buckingham theorem, as well as the choice of the system of basic units. The authors also include a presentation of model theory and similarity solutions. The target audience primarily comprises researchers and practitioners but the book may also be suitable as a textbook at university level.
Some Fundamentals of Dimenional Analysis -- Model Theory -- Illustrative Examples -- Similarity Solutions.
Keywords: Mechanical engineering; Mathematics -- Data processing; Mathematical physics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Mechanical Engineering; Computational Science and Engineering; Mathematical Methods in Physics; Engineering Thermodynamics, Heat and Mass Transfer; Engineering Fluid Dynamics